The Successful Return-To-Work Questionnaire for Cancer Survivors (I-RTW_CS): Development, Validity and Reproducibility - Greidanus, Michiel A. (Patient, 2020)
BACKGROUND: Cancer survivors’ perspectives on a successful return to work (RTW) may not be captured in the common measure of RTW, namely time until RTW. OBJECTIVE: The purpose of this study was therefore to develop an RTW outcome measure that reflects employed cancer survivors’ perspectives, with items that could be influenced by an employer, i.e. the Successful Return-To-Work questionnaire for Cancer Survivors (I-RTW_CS), and to assess its construct validity and reproducibility. METHODS: First, three focus groups with cancer survivors (n = 14) were organized to generate issues that may constitute successful RTW. Second, a two-round Delphi study among 108 cancer survivors was conducted to select the most important issues. Construct validity of the I-RTW_CS was assessed using correlations with a single-item measure of successful RTW and the Quality of Working Life Questionnaire for Cancer Survivors (QWLQ-CS; n = 57). Reproducibility (test–retest reliability) was assessed using the intraclass correlation coefficient (ICC; n = 50). RESULTS: Forty-eight issues were generated, of which seven were included: ‘enjoyment in work’; ‘work without affecting health’; ‘confidence of employer without assumptions about work ability’; ‘open communication with employer’; ‘feeling welcome at work’; ‘good work–life balance’; and ‘joint satisfaction with the situation (employer and cancer survivor)’. Correlations with single-item successful RTW and QWLQ-CS were 0.58 and 0.85, respectively. The reproducibility showed an ICC of 0.72. CONCLUSIONS: The I-RTW_CS provides an RTW outcome measure that includes cancer survivors’ perspectives and weights its items on an individual basis, allowing a more meaningful evaluation of cancer survivors’ RTW. This study provides preliminary evidence for its construct validity and reproducibility.